PARASITITASI Cotesia flavipes Cam. (Hymenoptera: Braconidae) TERHADAP LARVA Chilo auricilius Dudg. (Lepidoptera: Crambidae) DAN Chilo sacchariphagus Boj. (Lepidoptera: Crambidae) DI LABORATORIUM - Sisko Budianto; Maryani Cyccu Tobing; Hasanudin Hasanuddin (Universitas Sumatera Utara, 2014)
Sugarcane stem borers Chilo spp. are the important pests on sugarcane estate and need the seriouscontrolling. The using of parasitoid is the one of way to control the stem borers population whichsafe for environtment and human.The objectives of the research were to study the ability ofparasitoid C. flavipes on larvae of C. sacchariphagus and C. auricilius. The research was held atLaboratory of Sugarcane Research and Development Sei Semayang, Binjai, Medan, NorthSumatera from Mei until July 2013. The method used Randomized Complete Design with threefactors, the first factor was kind of host (C. sacchariphagus and C. auricilius), the second factorwas number of host (2, 3, 4 larvae) and the third factor was method of parasititation (artificial andnatural) with three replications. The results showed that method parasititation significantly effectedthe percentage of parasititation. The highest percentage of parasititation (40,83%) on artificialparasititation and the lowest (27,30%) on natural parasititation. The number of host significantlyeffected sex ratio. The sex ratio of male and female was 1 : 1,277.Keywords : Parasitoid, Cotesia flavipes, Chilo sacchariphagus, C. auricilius